2007
DOI: 10.1063/1.2766839
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferromagnetism in Fe-doped PbTiO3 nanocrystals

Abstract: Room-temperature ferromagnetism has been observed in Fe-doped PbTiO3 nanocrystals. The magnetism of the nanocrystals develops from diamagnetism to ferromagnetism and the paramagnetism on increasing nominal Fe doping concentration from 0to4mol%. Transmission electron microscope (TEM) and high-resolution TEM data indicate that Fe-doped PbTiO3 nanocrystals with the size of ∼100nm are organized to form a planarlike self-assembly via oriented aggregation. These assembled nanostructures effectively improve room-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 16 publications
6
73
1
1
Order By: Relevance
“…The values of the particle size as obtained from TEM/ SEM images are in good agreement with the one, calculated from XRD patterns. The observed particle size is much smaller than that reported by Ren et al 16 The significant reduction in particle size may be attributed to PVA as surfac- 19 reported that PVA when used as a surfactant is more efficient in surface modification and in reduction of particle size than polyethylene glycol as surfactant by Ren et al…”
Section: Methodscontrasting
confidence: 52%
See 1 more Smart Citation
“…The values of the particle size as obtained from TEM/ SEM images are in good agreement with the one, calculated from XRD patterns. The observed particle size is much smaller than that reported by Ren et al 16 The significant reduction in particle size may be attributed to PVA as surfac- 19 reported that PVA when used as a surfactant is more efficient in surface modification and in reduction of particle size than polyethylene glycol as surfactant by Ren et al…”
Section: Methodscontrasting
confidence: 52%
“…Palkar et al 15 have first observed magnetoelectric properties in ferroelectric PbTiO 3 by partially substituting Ti with Fe. Ren et al 16 showed room temperature ferromagnetism in Fe doped PbTiO 3 nanocrystals prepared by hydrothermal method using polyethylene glycol as surfactant. In our earlier work, we report enhance dielectric and ferromagnetic properties of Fe doped PbTiO 3 nanoparticles prepared by using polyvinyl alcohol ͑PVA͒ as a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…This value of coercive field is very small as compared to some Pb͑Fe, Ti͒O 3 system of nanoparticles. 9,15 The similar behavior was also found in Pb͑Fe, W͒TiO 3 system of thin film. 16 It is reported that the spin canting due to small distortion between Fe 3+ -O-Fe 3+ spins, results in weak ferromagnetism.…”
supporting
confidence: 65%
“…We have observed M s Ϸ 41.6 ϫ 10 −3 emu/ g ͑0.52 B / Fe͒ and H c ϳ 125 Oe for the specimen. The observed value of saturation magnetization is significantly higher than M s Ϸ 0.8ϫ 10 −3 emu/ g ͑0.01 B / Fe͒ reported by Ren et al 10 for their hydrothermal processed Fe doped nanocrystals ϳ100 nm using polyethylene glycol ͑PEG͒ as a surfactant. Improvement in ferromagnetic properties is due to the smaller particle's sizes in our specimens.…”
mentioning
confidence: 54%
“…Palkar and Malik 9 reported the conversion of a ferroelectric PbTiO 3 to a magnetoelectric system by partially substituting Ti with Fe. Ren et al 10 observed room temperature ferromagnetism in Fe-doped PbTiO 3 nanocrystals prepared by hydrothermal method using polyethylene glycol as a surfactant. However, further improvement in magnetic properties of Fe-doped PbTiO 3 is required to realize its actual use in magnetoelectric device applications.…”
mentioning
confidence: 99%